EKSPRESI NEGATIVE PENGGUNA SOSIAL MEDIA DALAM KARYA SENI INSTALASI YANG BERJUDUL EYE FOR AN I - Perwitasari, Dyah; Endriawan, Didit; Rachmawanti, Ranti (eProceedings of Art & Design, 2024)
Commonly every human have their own feelings and minds that only they knew. To show what9s inside their mind and feelings humans often project them through their expression directly or the opposite way. This is a sign to not mess around with human that kept their feelings by not projecting it directly and could potentially hide away their negative thoughts. The media that is used to craft this art work are literature study dan the medium exploration. . The art work message itself is to raise awareness over humans behind every gadget screen. It is to visualize the negative thoughts of other humans over what we actually posted in social media. Keywords : Eyes, Gadget, Installation Art, Negative Expression